Preschool attention and sleep support (PASS): protocol for a pilot feasibility randomized clinical trial - Davis, Naomi O.; Eichner, Brian; Gibson, Matthew J.; Lunsford-Avery, Jessica R. (Frontiers in Sleep, 2026)
IntroductionAttention-Deficit/Hyperactivity Disorder (ADHD) symptoms often emerge during preschool, highlighting a critical period for prevention. Preventative ADHD interventions may be most effective if they target biological mechanisms linked to core ADHD pathophysiology. Sleep dysregulation represents a potential target, yet the gold-standard behavioral intervention (behavioral parent training, BPT) focuses primarily on ameliorating daytime impairment. There is a critical need to adapt BPT to target behaviors across the 24-h period through integration with behavioral sleep medicine (BSM).MethodsThis trial will randomize children ages 3–5 years who are identified as at-risk for ADHD (i.e., with elevated ADHD symptoms) and their caregivers to receive either BPT (n = 22) or a combined intervention that includes BPT and BSM (Preschool Attention and Sleep Support, PASS; n = 22). Blinded assessments will be conducted at baseline, immediately post-treatment, and 3 months post treatment. Feasibility and acceptability will be assessed.ResultsKey outcomes will include changes in ADHD symptoms (measured by clinical and caregiver rating) and sleep (measured by both actigraphy and caregiver report). Changes in additional functional outcomes (e.g., comorbid symptoms, parenting stress) will be explored.DiscussionFindings from this study will provide essential data to inform a large-scale clinical trial of PASS, with the ultimate goal of improving functional outcomes among preschoolers at risk for ADHD and modifying the trajectory of this chronic condition through early preventative intervention focused on improving biological processes linked to ADHD.Trial RegistrationNCT05862727.